The Reach of Chronic-Disease Self-Management Education Programs to Rural Populations - Towne, Samuel D.; Smith, Matthew Lee; Ahn, SangNam; Ory, Marcia G. (Frontiers in Public Health, 2015)
This study assessed the sociodemographic characteristics of rural residents who participated in chronic-disease self-management education (CDSME) program workshops and the extent to which CDSME programs were utilized by those with limited access to health care services. We analyzed data from the first 100,000 adults who attended CDSME program workshops during a national dissemination spanning 45 states, the District of Columbia, and Puerto Rico. Approximately 24% of participants lived in rural areas. Overall, 42% of all participants were minorities; urban areas reached more minority participants (48%) than rural areas (25%). The average age of participants was high in rural (age, μ = 66.1) and urban (age, μ = 67.3) areas. In addition, the average number of chronic conditions was higher (p < 0.01) in rural (μ = 2.6 conditions) versus urban (μ = 2.4 conditions) areas. Successful completion of CDSME programs (i.e., attending four or more of the six workshop sessions) was higher (p < 0.01) in rural versus urban areas (78% versus 77%). Factors associated with higher likelihood of successful completion of CDSME programs included being Black (OR = 1.25) versus White and living in rural (versus urban) areas (OR = 1.09). Factors associated with lower likelihood of successful completion included being male (OR = 0.92) and residing in a primary care Health Professional Shortage Area or HPSA (versus a non-HPSA) (OR = 0.93). Findings highlight the capability of CDSME programs to reach rural residents, yet dissemination efforts can be further enhanced to ensure minorities and individuals in a HPSA utilize this program. Tailored strategies are needed to increase participant recruitment and retention in rural areas to overcome traditional barriers to health service access.